EFFORTS TO COMBAT MONEY LAUNDERING (RESEARCH STUDY OF MEDAN POLRESTABES) - Yasmirah Mandasari Saragih; Ilmuwani Lubis; Karolus Agung Dery Rianto; Irfan Rizky Pradya; Willy Novan Prakoso (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Money laundering, often known as money laundering, is carried out by government officials who hold the power to roll back money that is not legitimate after getting proceeds that are not theirs. In Indonesian, money laundering is translated by the term "money laundering" or "money bleaching". Article 3 of Law Number 8 of 2010 concerning Prevention and Eradication of Money Laundering Crimes states that Everyone who places, transfers, assigns, spends, pays, grants, deposits, takes abroad, changes forms, exchanges with currency or securities or acts other assets of which he knows or reasonably suspects constitute the proceeds of a crime with a maximum imprisonment of 20 (twenty) years and a maximum fine of Rp. 10,000,000,000.00 (ten billion rupiah). Based on research at the Criminal Investigation Unit of the Medan Police Criminal Investigation Unit, there was a crime of money laundering. However, in reality the settlement of money laundering crimes still faces obstacles. This study aims to explain the law enforcement process by the Criminal Investigation Unit of the Medan Polrestabes in the crime of money laundering, the efforts made by the Criminal Investigation Unit of the Medan Police in tackling money laundering and the obstacles faced by the Criminal Investigation Unit of the Medan Police in tackling money laundering. Data in the completion of this scientific work was carried out using empirical legal research methods by collecting primary data obtained by interviewing respondents and information, while library data was obtained by studying laws and regulations, textbooks, scientific writings, and literature related to the problems discussed in this study. It is recommended to increase the quantity and quality of police personnel and complete the facilities needed by the police as well as increase the budget used to handle cases. As for the inhibiting factors of the Police in tackling money laundering crimes, namely internal factors are law enforcement factors while external factors are legal factors, facilities and infrastructure factors, community factors and cultural factors. It is recommended to increase the quantity and quality of police personnel and complete the facilities needed by the police as well as increase the budget used to handle cases.